Squamous cell carcinoma in the kidney, a case report - Castro Pizarro, Hugo (2015)
Presence of a squamous cell carcinoma in the urinary system is an infrequent event. This neoplasm has an incidence of 1.4 percent among renal cancer. In this presentation we have the results of an autopsy of a 78 years old male with a squamous cell carcinoma that compromises renal tissue. The case is completed with a brief revision about the topic, including pathologic and histologic characteristics of the neoplasm.